Color Atlas of Pediatric Anatomy, Laparoscopy, and Thoracoscopy - McHoney, Merrill; Kiely, Edward M.; Mushtaq, Imran; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2017)
This atlas of anatomy and operative techniques provides a thorough outline of the procedures commonly used in laparoscopic and thoracoscopic pediatric surgery. Step-by-step operative photographs are accompanied by explanatory text, and line diagrams are used to highlight the important anatomy as seen endoscopically. Alternative techniques, instruments, and steps are described when appropriate, and attention is drawn to highlights and pitfalls. While each chapter includes some basic background on the condition in question, the focus is very much on the operative procedures. Color Atlas of Pediatric Anatomy, Laparoscopy, and Thoracoscopy is ideal for those establishing a laparoscopic practice as well as for those in training who wish to embark on minimally invasive surgery. It also serves as a supplementary atlas of anatomy and surgical technique for younger surgeons and medical students. .
1. Introduction and General Principles -- 2. Equipment and Ergonomics -- 3. Thoracoscopic Debridement of Empyema -- 4. Spontaneous Pneumothorax -- 5. Thoracoscopic Lung Biopsy and Segmentectomy -- 6. Thoracic Sympathectomy -- 7. Thymectomy -- 8. Mediastinal Cysts.-9. Thoracoscopic Nuss Procedure -- 10. Oesophageal Atresia and Tracheoesophageal Fistula -- 11. Thorascopic Aortopexy -- 12. Thoracoscopy for Congenital Lung Malformations -- 13. Thoracic Neuroblastoma -- 14. Thoracoscopic Placation for Eventration of the Diaphragm -- 15. Laparoscopic Repair of Morgani Hernia -- 16. Primary Button Gastrostomy -- 17. Laparoscopic Thal Fundoplication -- 18. Pyloric Stenosis -- 19. Duodenal Atresia Repair -- 20. Meckel Diverticulum -- 21. Laparoscopy for Intussusception -- 23. Laparoscopic Cholecystectomy -- 24. Laparoscopic Splenectomy -- 25. Laparoscopic Surgery for Choledochal Cysts -- 26. Laparoscopic Colectomy -- 27. Laparoscopic Duhamels Pullthrough for Hirschprung Disease -- 28. Laparoscopy-Assisted Soave Pullthrough for Hirschprung Disease.-29. Laparoscopy-Assisted Swenson-like Transanal Pullthrough for Hirschprung Disease -- 30. Inguinal Herniotomy -- 31. Undescended Testis: Laparoscopic Fowler-Stephens Orchidopexy -- 32. Laparoscopic Varicocelectomy -- 33. Retroperitoneoscopic Adrenalectomy -- 34. Laparoscopic Nephrectomy -- 35. Retroperitoneoscopic Nephrectomy/Heminephrectomy -- 36. Pyeloplasty.-.
Keywords: Medicine; Human anatomy; Abdominal surgery; Minimally invasive surgery; Pediatric surgery; Thoracic surgery; Medicine & Public Health; Pediatric surgery; Minimally invasive surgery; Anatomy; Thoracic surgery; Abdominal surgery